A Precious Diagnostic "Pearl": The Necklace Pattern in Germ Cell Tumors of the Testis. (April 2018) - Snow, Justin; Mosquera, Juan Miguel; Scognamiglio, Theresa; Robinson, Brian D.; Khani, Francesca
Diffuse embryoma is a rare pattern of nonseminomatous germ cell tumor of the testis originally described in 1983. We report a case with this predominant pattern in an 18-year-old male with a painless palpable testicular mass. Although it is relatively common to see a diffuse embryoma pattern focally in mixed nonseminomatous germ cell tumors of the testis, it is rarely the predominant pattern and can represent a diagnostic pitfall on routine hematoxylin and eosin stain. We emphasize the importance of recognizing the individual components within the diffuse embryoma pattern, review the literature, and briefly discuss the ancillary immunohistochemical stains that may be utilized to help support the diagnosis.